Impact of diabetes mellitus status on coronary pathoanatomy and interventional treatment: insights from the Euro heart survey PCI registry - Bauer, Timm; Möllmann, Helge; Weidinger, Franz; Zeymer, Uwe; Seabra-Gomes, Ricardo; Eberli, Franz; Serruys, Patrick; Vahanian, Alec; Silber, Sigmund; Wijns, William; Hochadel, Matthias; Nef, Holger M.; et al. (Catheterization and cardiovascular interventions, 2011)
Objectives: The present analysis was performed to evaluate the impact of diabetes mellitus (DM) status on the severity of coronary artery disease (CAD) and current approaches in interventional treatment. Background: Little is known about the effect of DM treated with diet, oral agents, or insulin on lesion characteristics and anatomical pattern of CAD and their interventional treatment. Methods and results: Patients (n = 46,779) of the contemporary Euro Heart Survey PCI registry with known DM status were included in this analysis. Nondiabetics (n = 35,280, 75.4%) were compared with diabetics treated with diet (n = 1,533, 3.3%), oral agents (n = 7,222, 15.4%), and insulin (n = 2,744, 5.8%). Diabetic patients were older, suffered more frequently from comorbidities and presented more often with cardiogenic shock. The number of severely stenosed (≥70%) segments incrementally increased from nondiabetics to insulin-requiring diabetics. The location of lesions did not differ between patients with and without DM. The ratio stenosed/treated segments progressively rose among the four patient cohorts. The severity of DM negatively correlated with the extent of complete revascularization. After adjustment for confounding variables no significant differences in hospital mortality could be observed between patients without DM and diabetics treated with diet, but a significantly higher rate of death was seen in diabetic patients with oral medication and insulin therapy. Conclusions: Although CAD was more severe in patients with DM the percentage of treated segments with ≥70% stenosis was lower. Adjusted hospital mortality was increased among diabetics treated with oral medication or insulin, but not among those treated with diet. © 2011 Wiley-Liss, Inc.